Investigating paranasal sinuses developmental disorders and septum deviation angle effects on olfactory fossa depth using cone-beam computed tomography - Hoda Haerian; Roshanak Ghaffari; Shabnam Azari (Dental Research Journal)
Background: The ethmoid roof separates the ethmoid cells from the anterior cranial fossa. From the medial side, the roof of the ethmoid is connected to the lateral lamella of the ethmoid plate, which is the thinnest bone at the base of the skull and is most vulnerable to damage during endoscopic surgeries. The purpose of this study is to investigate the height of the lateral lamella in patients with hypoplasia/aplasia of the paranasal sinuses and deviation of the nasal septum using reconstructed multiplanar images by cone-beam computed tomography (CBCT). Materials and Methods: In this descriptive-analytical (cross-sectional) study, 192 CBCT images (89 males and 103 females) with an age range of 18 years and older were examined. These 192 participants included 58 cases of frontal sinus (FS) hypoplasia/aplasia, 42 cases of maxillary sinus (MS) hypoplasia/aplasia, 12 cases of sphenoid sinus (SS) hypoplasia/aplasia, 40 cases of nasal septum deviation, and 40 cases as a control group. As Keros classification indicates, the depth of the olfactory fossa was estimated in three categories: type 1 (1–3 mm), type 2 (4–7 mm), and type 3 (8–16 mm). The height of the lateral lamella was measured in the coronal section in all images. The septum deviation angle was also measured in the coronal section. For statistical analysis, Shapiro–Wilk, independent t, nonparametric Mann–Whitney, Pearson correlation, and Kruskal–Wallis tests were done using the SPSS 22 software. Results: The most common type of olfactory fossa in all disorders and the control group was type II of the Keros classification. The highest average lateral lamella height was in the SS hypoplasia group (6.226 mm) and the lowest in the FS aplasia group (4.411 mm). The lateral lamella height in FS aplasia/hypoplasia groups was significantly lower than the control group (P = 0.002 and P = 0.044). The average deviation angle of the nasal septum was 19.73° ±5.35° and no significant relationship was found between this angle and the height of lateral lamella (P = 0.938). The height of the lateral lamella in the FS hypoplasia group was significantly higher in men than in women (P = 0.019), but in other groups, there was no relationship between lateral lamella height and gender. Seventy-five percent of the participants of the nasal septum deviation group were type II of Keros classification and the remaining 25% were type I. Conclusion: The lateral lamella height in hypoplastic/aplastic FSs is lower than normal, and this information is useful in preventing complications during endoscopic sinus surgery.